High dependency renal unit for the management of COVID-19 in patients with severe acute or chronic kidney disease. Issue 35 (2nd September 2022) - Thakare, Sayali; Modi, Tulsi; Gandhi, Chintan; Bose, Sreyashi; Deb, Satarupa; Katyal, Abhinav; Saxena, Nikhil; Patil, Ankita; Patil, Sunil; Pajai, Atim; Bajpai, Divya; Jadhav, Pratap; et al.
Abstract : Coronavirus disease 2019 (COVID-19) in patients with severe impairment of kidney function is associated with high mortality. We evaluated the effect of high dependency renal unit (HDRU), with nephrologists as primary care physicians, as a quality improvement initiative for the management of these patients. This was a quasi-experimental observational study conducted at a tertiary care hospital in western India. Patients hospitalized for COVID-19 with pre-existing end-stage-renal-disease and those with severe AKI requiring dialysis (AKI-D) were included. For the first 2 months, these patients were cared for in medical wards designated for COVID-19, after which HDRU was set up for their management. With nephrologists as primary care providers, the 4 key components of care in HDRU included: care bundles focusing on key nephrology and COVID-19 related issues, checklist-based clinical monitoring, integration of multi-specialty care, and training of nurses and doctors. Primary outcome of the study was in-hospital mortality before and after institution of the HDRU care. Secondary outcomes were dialysis dependence in AKI-D and predictors of death. A total of 238 out of 4254 (5.59%) patients with COVID-19, admitted from 28th March to 30th September 2020, had severe renal impairment (116 AKI-D and 122 end-stage-renal-disease). 145 (62%) had severe COVID-19. From 28th May to 31st August 2020, these patients were managed in HDRU. Kaplan–Meier analysis showed significant improvement in survival during HDRU care [19 of 52 (36.5%) in pre-HDRU versus 35 of 160 (21.9%) in HDRU died, P ≤ .01]. 44 (67.7%) AKI-D survivors were dialysis dependent at discharge. Breathlessness and altered mental status at presentation, development of shock during hospital stay, and leukocytosis predicted mortality. HDRU managed by nephrologists is a feasible and potentially effective approach to improve the outcomes of patients with COVID-19 and severe renal impairment.